(untitled) (Baghdad Science Journal, 2004)
The effect of some environment faetor (different temperature and relative humidity) on the biology of the old world- screw worm, were studied under laboratory condition, the result showed that non of the eggs hatched at 15°c and under dried eondition which relative humidity between 20-40%, also result showed that the mature larvae needs one days to become pupa since it leaves the larval died at the temperature ranged between 25-40°C at different humidity rates. While it needs 3 days under lower temperature and different humidity to become pu^, on the other hand the results showed that either low temperature and dried condition or high temperature at different humidity rates cause non of pupa became adult. While low temperature (15-20) °c at suitable humidity rate will elongate pupal, further more it is also noticed that the suitable temperature ??’? pupa? development ranged between 25- 35°C under different relative humidity rate and it ranged between 5-8 days.